Diagnosis and Treatment of Urinary Tract Complication in Crohn's Disease: An Experience over 15 Years. (2002) - Ben-Ami, Haim; Ginesin, Yeoshua; Behar, Doron M; Fisher, Doron; Edoute, Yeouda; Lavy, Alexandra
Abstract : BACKGROUD: Urinary tract complications in Crohn's disease are common but treatable, and often present diagnostic and therapeutic dilemmas. PURPOSE: To determine the incidence of urinary tract complications in patients with Crohn's disease in Israel and to report an experience over 15 years of patients with Crohn's disease, with the aim of illustrating the diverse patterns of presentation, and thereby broadening the approach to diagnosis and treatment. METHODOLOGY: Clinical and radiological findings of 312 patients with Crohn's disease were reviewed. RESULTS: Simple cystitis was the most common problem, occurring in 51 patients. The problem seldom required hospitalization and was instead managed in the ambulatory setting. A review revealed that 22 patients with urinary tract complications required hospitalization. Six patients had ileovesical fistulas. In one patient, the colon was also affected. In another patient, radiological and endoscopic studies failed to identify the fistula, which was confirmed during surgery. All six patients were treated surgically. Four patients had ureteral obstructions and hydronephrosis, three of whom responded well to conservative treatment. In one patient, the affected ileal segment was resected. Four patients suffered from retroperitoneal abscess accompanied by urinary symptoms. Twelve patients developed right kidney stones. All of the patients suffered from long-standing Crohn's disease with bowel resection. Surprisingly, most of the severe complications occurred in men, although 70% of the patients were women. CONCLUSIONS: Based on these findings, urological complications are not rare in patients with Crohn's disease, and necessitate a high degree of diligence and periodic urological evaluation.